Dissemination of multidrug resistant Acinetobacter baumannii in various hospitals of Antananarivo Madagascar - Carod Jean-François; Ramparany Lovasoa; Randrianirina Frédérique; Rakotonirina Hanitra C; Ratsima Elisoa; Andriamanantena Tahiry S; Richard Vincent; Talarmin Antoine (BMC, 2010)
Abstract This study reports the dissemination of multidrug-resistant (MDR) OXA-23-producing Acinetobacter baumannii clones in hospitals in Antananarivo, Madagascar. A total of 53 carbapenem-resistant A. baumannii isolates were obtained from September 2006 to March 2009 in five hospitals. These resistant strains represent 44% of all A. baumannii isolates. The double disk synergy test was performed to screen for production of metallo-beta-lactamases. Polymerase chain reaction (PCR) and DNA sequencing were performed for the detection of bla(AmpC), bla(OXA-51),bla(OXA-23), bla(OXA-24), bla(IMP), bla(VIM). The presence of the insertion sequence ISAba1 relative to blaOXA-23 and blaOXA-51 was assessed by PCR. Isolates were typed by Rep-PCR. All the isolates were MDR and produced the OXA-23 carbapenemase, which was confirmed by sequencing. PCR analysis for AmpC and OXA-51 gave positive results for all strains studied. No isolates produced metallo-beta-lactamases. In all isolates ISAba1 laid upstream of blaOXA-23. The A. baumannii isolates were separated into two genotypes; genotype A had a higher prevalence (41 strains) than genotype B (12 strains). Genotype A was present in four hospitals, whilst genotype B had spread in two hospitals. The high frequency of MDR OXA-23-producing A. baumannii in various hospitals in Antananarivo is curious since carbapenems are not available in Madagascar, but it emphasises the need for infection control procedures and strict adherence to them to prevent the spread of these resistant organisms in Antananarivo and also the need to control the use of carbapenems in the future.